Educational needs among stroke patients admitted to Hospital Universiti Sains Malaysia: preliminary findings (keperluan pendidikan dalam kalangan pesakit strok di Hospital Universiti Sains Malaysia: data awalan) - Sowtali, Siti Noorkhairina; Harith, Sakinah (Fakulti Sains Kesihatan and Penerbit UKM, 2014)
This study was conducted to determine types of educational needs among stroke patients admitted to Hospital Universiti Sains Malaysia. Stroke patients (n = 41) were conveniently recruited from Medical and Surgical Ward between September to December 2012. Data were obtained using semi-guided administered questionnaires and from the medical reports. Patients were given adequate time to complete the lifestyle history and educational needs on stroke with researcher’s assistance. Instrument on the educational needs consisted of fi ve themes including general information on stroke, management of risk factors, treatments of stroke, rehabilitation and post-stroke problems and post-stroke diet management. Findings indicated majority of the stroke patients were female (58.5%), between 56 to 65 years old (39.0%) and diagnosed with ischemic stroke (68.3%). Patients had history of hypertension (85.4%), diabetes (46.3%), hyperlipidemia (29.3%), ischemic heart disease (22.0%) and atrial fi brillation (2.4%). Eleven of them (26.9%) were ex-smokers and many practice unhealthy lifestyle such as lack of exercise (80.5%) and prefer fried foods (68.3%). Most patients were on multiple pharmacotherapies (92.7%) to treat their medical conditions. Educational needs rated highest need to know among stroke patients were on prevention (92.7%), fi rst aid management (85.4%), complications (85.4%) and recurrence (85.4%) of stroke in general. Other concerned were about possibility of cure with drug (92.7%), range of motion exercise (82.9%), fi sh intake (78.0%), fruit and vegetable consumption (78.0%) after stroke. Findings from this study provide a baseline information on types of educational needs among stroke patients. More patient educational intervention on primary and secondary stroke prevention should be structured in hospital and community settings in the future.